(untitled) (Research, Society and Development, 2022)
The use of the category “race” in population surveys helps in the understanding of existing ethnic-racial inequalities in Brazilian society. However, in studies focused on food and nutrition, there is an information gap. To evaluate the insertion of the category “race” in studies based on epidemiological surveys related to food and nutrition. A manual search of population surveys that used the category race and food theme and nutrition was carried out, resulting in 47 publications. Subsequently, the Banco Virtual de Saúde database was consulted using Medical Subject Headings (DeCs/MeSH). After elimination of duplicity and application of eligibility criteria (research objective, text in portuguese and full text), without delimiting the date of publication, 24 studies remained. The race was inserted from the categories white, black, brown, indigenous, yellow, and undeclared. Was evident the grouping of blacks and browns, or whites and non-whites. Since 2003, studies related to food, nutrition and race were evidenced. The main themes developed were related to food insecurity, use of infant formula, breastfeeding, nutritional status and food consumption. There are limitations to the discussion of the theme. The analysis of the nutrition of socially racially vulnerable groups is just possible through population surveys that include the category “race”.